Prospective techno-economic and environmental assessment of carbon capture at a refinery and CO2 utilisation in polyol synthesis. (October 2017) - Fernández-Dacosta, Cora; van der Spek, Mijndert; Hung, Christine Roxanne; Oregionni, Gabriel David; Skagestad, Ragnhild; Parihar, Prashant; Gokak, D.T.; Strømman, Anders Hammer; Ramirez, Andrea
Highlights: Assessment of carbon capture at refinery, storage or utilization in polyol synthesis. Techno-economic and environmental assessments integrated with uncertainty analysis. Improved business case CO2 capture and partial utilisation over capture and storage. CO2 utilisation and partial storage reduces climate change compared to no CO2 capture. Abstract: CO2 utilisation is gaining interest as a potential element towards a sustainable economy. CO2 can be used as feedstock in the synthesis of fuels, chemicals and polymers. This study presents a prospective assessment of carbon capture from a hydrogen unit at a refinery, where the CO2 is either stored, or partly stored and partly utilised for polyols production. A methodology integrating technical, economic and environmental models with uncertainty analysis is used to assess the performance of carbon capture and storage or utilisation at the refinery. Results show that only 10% of the CO2 captured from an industrial hydrogen unit can be utilised in a commercial-scale polyol plant. This option has limited potential for large scale CO2 mitigation from industrial sources. However, CO2 capture from a hydrogen unit and its utilisation for the synthesis of polyols provides an interesting alternative from an economic perspective. The costs of CO2 -based polyol are estimated at 1200 €/t polyol, 16% lower than those of conventional polyol. Furthermore, the costs of storing the remaining CO2 are offset by the benefits of cheaper polyol production. Therefore, the combination of CO2 capture and partial utilisation provides an improved business case over capture and storage alone. The environmental assessment shows that the climate change potential of this CO2 utilisation system is 23% lower compared to a reference case in which no CO2 is captured at the refinery. Five other environmental impact categories included in this study present slightly better performance for the utilisation case than for the reference case.